Aspects of environmentally beneficial tax incentives: A literature review - Angela Köppl; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2021)
While environmental taxes aim at making environmentally harmful behaviour more costly, the opposite is true for environmentally beneficial tax incentives. Tax incentives imply foregone public revenues to favour less polluting consumption and investment activities in order to achieve environmental policy goals. While there is a large body of theoretical literature on environmental taxes and emissions trading, the theoretical literature on environmentally beneficial tax incentives (as well as direct subsidies) is rather slim. Most of the literature in the field of beneficial tax incentives consists of empirical case studies on concrete tax incentives that have been introduced in individual countries. The paper provides a review of theoretical and empirical literature addressing the effects of environmentally beneficial tax incentives. Hereby, the review of empirical evidence on the impact of specific tax incentives to reduce greenhouse gas emissions focuses on tax incentives in the transport sector and particularly on those attached to vehicle taxation aiming at supporting the decarbonisation of the car fleet. We also summarise the sparse empirical evidence on tax incentives intended to support the use of public transport, green R&D, and energy efficiency.
Keywords: H23; Q54; Q58; 330; Carbon taxation; environmental taxation; price-based instruments; tax incentives; climate policy